THE MAIN METHODS OF CORRECTING COMMUNICATIVE ACTIVITY IN CHILDREN WITH SPEECH IMPAIRMENT - Shamsieva Sevara Yusupovna (Journals Park Publishing, 2024)
The article highlights the main methods for correcting communicative activity in children with speech impairment. Effective rules of communication, hearing skills and work activity of a speech pathologist are analyzed.
Keywords: children with speech impairment, communicative activity, correction, rule, skill, interactive games technologist, organizer, consultant, presenter.